PHYSICOCHEMICAL CHARACTERIZATION AND THERMAL DECOMPOSITION OF GARIN MAIGANGA COAL - Nyakuma, Bemgba Bevan; Jauro, Aliyu (GeoScience Engineering, 2016)
The paper examined the physicochemical and thermal characteristics of the recently discovered Garin Maiganga (GMG) coal from Nigeria. Physicochemical characterization comprised of elemental, proximate, calorific value and classification (rank) analyses. Thermogravimetric (TG) analysis was examined at 20 °C/min from 30–1000 °C under inert conditions to characterize the thermal devolatilization behaviour and temperature profile characteristics (TPC). The results indicated that GMG coal comprises low ash, Nitrogen and Sulphur content. Moisture content was > 5 wt. %, volatile matter > 50 wt. %, fixed carbon > 22 wt. % and heating value (HHV) of 23.74 MJ/kg. Based on HHV and physicochemical properties, GMG coal was classified as Sub-Bituminous B, non-agglomerating low rank coal (LRC). The GMG coal TG profile characteristics; onset, peak and offset temperature were; 382.70 °C, 454.60°C and 527.80 °C, respectively. The DTG profile revealed four (4) endothermic peaks corresponding to drying, decomposition of volatile matter and coke formation. The residual mass of 50.16 wt. % (total weight loss 49.84 %) indicates temperatures above 1000 °C are required for complete pyrolytic decomposition. In conclusion, the results indicate GMG is potentially suitable for future utilization in electric power generation and the manufacture of cement and steel.